Paradoks Hukum Noodweer: Penerapan Pasal 49 KUHP dan Kedudukan Korban Begal yang Dijadikan Tersangka dalam Sistem Peradilan Pidana Indonesia - Sheren Dwi Oktaria; Inggit Setya Ningrum; Nadia Wiratama Jasmine; Dwi Mulyati (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2025)
Abstract: This study examines the legal paradox in the application of the concepts of noodweer and noodweer excess in Indonesia, particularly related to the phenomenon of victims of robbery who are named suspects after defending themselves. The study focuses on three cases that occurred in Indonesia, namely the case of Amaq Sinta in Central Lombok (NTB), DI in Medan (North Sumatra), and ZA in Malang (East Java). All three cases demonstrate the complexity of law enforcement between self-defense efforts and the limits of actions considered proportional under criminal law. Analysis of these three cases shows that the application of Article 49 of the Criminal Code often leads to incidents, especially in determining the elements of proportionality, subsidiarity, and the condition of "urgency" in self-defense. Although morally the perpetrators are considered to be defending themselves from a real threat, legally such actions can be categorized as excessive if they exceed the limits of reasonableness, for example due to emotion, fear, or the use of excessive violence. This paradox reveals a lack of synchronicity between formal justice and substantive justice in the Indonesian criminal system. From a normative perspective, clearer legal guidelines are needed regarding self-defense, particularly in the context of street crimes that endanger the victim's life. This study recommends reformulating the guidelines for investigation and prosecution so that the legal system no longer criminalizes self-defense actions taken in emergency situations and situations of psychological stress.Keywords: Noodweer, Noodweer Excesses, Self-Defense, Mugging Victims, Legal Paradox, Indonesian Criminal System.Abstrak: Penelitian ini membahas paradoks hukum dalam penerapan konsep noodweer dan noodweer exces di Indonesia, khususnya terkait dengan fenomena korban tindak pidana pembegalan yang justru ditetapkan sebagai tersangka setelah melakukan pembelaan diri. Fokus kajian diarahkan pada tiga kasus yang terjadi di Indonesia, yakni kasus Amaq Sinta di Lombok Tengah (NTB), DI di Medan (Sumatera Utara), dan ZA di Malang (Jawa Timur). Ketiganya menunjukkan kompleksitas penegakan hukum antara upaya mempertahankan diri dengan batas-batas tindakan yang dianggap proporsional menurut hukum pidana. Analisis terhadap ketiga kasus menunjukkan bahwa penerapan Pasal 49 KUHP seringkali menimbulkan perdebatan, terutama dalam menentukan unsur proporsionalitas, subsidiaritas, dan kondisi “terdesak” dalam pembelaan diri. Meskipun secara moral para pelaku dianggap membela diri dari ancaman nyata, secara yuridis tindakan tersebut dapat dikategorikan sebagai noodweer exces apabila melampaui batas kewajaran, misalnya karena adanya emosi, kepanikan, atau penggunaan kekerasan berlebihan. Paradoks ini mengungkap adanya ketidaksinkronan antara keadilan formal dan keadilan substansial dalam sistem peradilan pidana Indonesia. Dari perspektif normatif, diperlukan pedoman hukum yang lebih jelas terkait pembelaan diri, terutama dalam konteks kejahatan jalanan yang membahayakan nyawa korban. Penelitian ini merekomendasikan reformulasi pedoman penyidikan dan penuntutan agar sistem hukum tidak lagi mengkriminalisasi tindakan pembelaan diri yang dilakukan dalam situasi darurat dan penuh tekanan psikologis.Kata Kunci: noodweer, noodweer exces, pembelaan diri, korban begal, paradoks hukum, sistem peradilan pidana Indonesia.